THE APPLICATION OF PROCESS SKILLS APPROACH IN LEARNING READING EXPLANATION TEXT IN GRADE 11 OF MA DARUL HIKMAH PEKANBARU - Desi Puspita Sari; Abdul Razak; Charlina (Jurnal PAJAR (Pendidikan dan Pengajaran), 2020)
The study aims to determine the effect of process skills approach in learning reading explanation text in grade 11 of MA Darul Hikmah Pekanbaru. The method used was a quantitative research method with an experimental research model. The design of this research was one group pret estpostest design. Sampling techniques used was simple random sampling. The population in this study was 78 students with 65 students were chosen as the samples. Data collection technique used multiple choice with 20 questions. This test was used to assess student’s reading skills. Data analysis techniques used the lilifors normality test and chi-square test, then tested the hypothesis using the one-sample test, one-way ANOVA, and two-way ANOVA. The average pretest scores in the control class were 7.65, while the average pretest scores in the experimental class were 6.25. The average postest scores in the control class were 8.9, while the average postest scores in the experimental class were 6.8. The findings showed that there was significant effect of the application of the process skills approach toward learning reading explanation texts in grade 11 students of MA Darul Hikmah Pekanbaru.